2019
DOI: 10.1093/ofid/ofz176
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Breakthrough Invasive Mold Infections in Acute Myeloid Leukemia Patients Receiving Remission Induction Chemotherapy

Abstract: Background Despite fungal prophylaxis, invasive mold infections (IMIs) are a significant cause of morbidity and mortality in patients with acute myeloid leukemia (AML) receiving remission induction chemotherapy. The choice of antifungal prophylaxis agent remains controversial, especially in the era of novel targeted therapies. We conducted a retrospective case–control study to determine the incidence of fungal infections and to identify risk factors associated with IMI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
1
7
1
Order By: Relevance
“…The incidence of breakthrough IFI in our study was approximately 6%, which was slightly higher than the results from other previous studies in recent years. 29 , 42–44 Aspergillosis was the leading cause of breakthrough IFI (53.8%), similar to other studies. 45 , 46 Contrarily, our result differed from a 4-year retrospective study from France showed that mucormycosis and fusariosis were the leading cause of breakthrough IFI.…”
Section: Discussionsupporting
confidence: 89%
“…The incidence of breakthrough IFI in our study was approximately 6%, which was slightly higher than the results from other previous studies in recent years. 29 , 42–44 Aspergillosis was the leading cause of breakthrough IFI (53.8%), similar to other studies. 45 , 46 Contrarily, our result differed from a 4-year retrospective study from France showed that mucormycosis and fusariosis were the leading cause of breakthrough IFI.…”
Section: Discussionsupporting
confidence: 89%
“…The epidemiology of IFI over the last two decades is almost the same in existing studies [ 25 , 26 , 27 ]. However, in a manner different from our results, with high rates of invasive Aspergillosis, the current scenario in the era of new azoles anti-mold prophylaxis is a trend of a shift from aspergillus species to non-aspergillus species [ 17 , 28 , 29 ].…”
Section: Discussioncontrasting
confidence: 98%
“…Another major limitation is that cultures remain negative in up to 75% of patients diagnosed with IA. 38 However, other, faster methods are available. The AsperGenius ® (Pathonostics, Maastricht, the Netherlands) PCR assay has proven useful in identifying the two most common genetic markers of triazole resistance (TR34/L98H; TR46/Y121F/T289A) and can be used directly on bronchoalveolar lavage (BAL) fluid, with results available on the day of testing.…”
Section: Resultsmentioning
confidence: 99%